Van siters en skalmeie - Barnard-Naude, Alfred Jacobus (Department of English Language and Literature, 2014)
This dissertation addresses the (often controversial) relationship between poetry and philosophy in the context of the Afrikaans poetic heritage. It consists of two components: a portfolio of own poetry and an essay in which it is argued that against the backdrop of the poststructural zeitgeist, the relationship between poetry and philosophy should be understood as a deconstructive one.